A study of Price levels between Pure play e-retailers and Bricks and clicks retailers. - Pugla, Ankit (2007)
Price Levels on the Internet have attracted a lot of research and managerial attention. Similar to initial predictions that Internet would lead to lower prices, empirical research shows that online prices are lower than conventional stores. There have been few studies comparing price levels at online and offline retailer, but not much is known about how prices compare among pure play e-retailers and bricks and clicks (multichannel) retailers. This research addresses this important issue through an analysis of price levels in the Mp3 player market among two types of retailers in UK. The result in this study, based on analysis of 212 different retailers, shows that when prices both excluding delivery charges and including delivery charges are considered bricks and clicks retailers have high prices than pure-play e-retailers. Additionally, this study finds that Price level is positively related to the quality of the Mp3 player. This study also finds that as number of sellers for a particular Mp3 player increases, price (excluding and including delivery charges) increases. Thus contradicting the general phenomenon that increase in number of seller will intensify competition and ultimately decrease the prices of a particular product.